ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL POLA BILANGAN DI KELAS VIIIC SMP NEGERI 3 BANAWA: Analysis Of Student’s Errors In Solving Number Pattern Problems In Class VIIIC Of SMP Negeri 3 Banawa - Anggriani; Hasbi, Muh.; Hadjar, Ibnu (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
The study is a qualitative research that aims to describe the students' mistakes in solving number pattern problems in class VIII C SMP Negeri 3 Banawa. The subjects of this study were 2 students drawn from 15 grade VIII C students at SMP Negeri 3 Banawa for the 2022/2023 school year who had studied number pattern material. The selection subjects of this study took into consideration, namely: (1) two students made more mistakes than other students, (2) had different mistakes, (3) mistakes could represent mistakes made by other students, (4) students could communicate well, and (5) recommendations from mathematics teachers of SMP Negeri 3 Banawa. The data collection techniques used are assignments and interviews. The analysis in this study used the Newman stage. The results of this study show several errors experienced by students in solving number pattern problems, namely: (1) Transformation error, namely students are wrong in determining the formula in and do not know the formula to be used in solving the problem, (2) Process ability error, namely students do not change Un to U12 and Un to U15, and students are wrong in performing calculation operations, (3) Error writing the final answer, namely students do not know and do not write the final conclusion.